Children's Heart Assessment Tool for Transplantation (CHAT) Score: A Novel Risk Score Predicts Survival After Pediatric Heart Transplantation. Issue 3 (May 2019) - Fraser, Charles D.; Grimm, Joshua C.; Zhou, Xun; Lui, Cecillia; Giuliano, Kate; Suarez-Pierre, Alejandro; Crawford, Todd C.; Magruder, J. Trent; Hibino, Narutoshi; Vricella, Luca A.
Background: Given the shortage of donor organs in pediatric heart transplantation (HTx), pretransplant risk stratification may assist in organ allocation and recipient optimization. We sought to construct a scoring system to preoperatively stratify a patient's risk of one-year mortality after HTx. Methods: The United Network for Organ Sharing database was queried for pediatric (<18 years) patients undergoing HTx between 2000 and 2016. The population was randomly divided in a 4:1 fashion into derivation and validation cohorts. A multivariable logistic regression model for one-year mortality was constructed within the derivation cohort. Points were then assigned to independent predictors ( P < .05) based on relative odds ratios (ORs). Risk groups were established based on easily applicable, whole-integer score cutoffs. Results: A total of 5, 700 patients underwent HTx; one-year mortality was 10.7%. There was a similar distribution of variables between derivation (n = 4, 560) and validation (n = 1, 140) cohorts. Of the 12 covariates included in the final model, nine were allotted point values. The low-risk (score 0-9), intermediate-risk (10-20), and high-risk (>20) groups had a 5.18%, 10%, and 28% risk of one-year mortality ( P < .001), respectively. Both intermediate-risk (OR = 2.46, 95% confidence interval [95% CI]: 1.93-3.15; P < .001) and high-risk (OR = 9.24, 95% CI: 6.92-12.35; P < .001) scores were associated with an increased risk of one-year mortality when compared to the low-risk group. Conclusions: The Children's Heart Assessment Tool for Transplantation score represents a pediatric-specific, recipient-based system to predict one-year mortality after HTx. Its use could assist providers in identification of patients at highest risk of poor outcomes and may aid in pretransplant optimization of these children.